NATIONAL INTEGRITY DISCOURSE IN THE CURRICULUM OF KHYBER PAKHTUNKHWA: AN ANALYSIS - Muhammad Yasir; Hina Rehman; Asad Ullah (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examines the incorporation of national integrity discourse in Khyber Pakhtunkhwa’s (KP) curriculum, essential for fostering unity and patriotism. Through qualitative analysis of official curriculum documents, including textbooks and policies, this research evaluates the representation of national integrity values. It assesses areas such as national history, cultural diversity, civic education, and citizenship rights, aiming to align curriculum content with government objectives of promoting unity and tolerance. While KP’s curriculum partly reflects government objectives, gaps exist in comprehensive coverage of cultural diversity and citizenship rights. Additionally, there’s scope to enhance critical thinking and ethical reasoning components. Addressing curriculum deficiencies is crucial to effectively instilling national integrity. Collaboration among policymakers, educators, and curriculum designers is necessary to bridge these gaps, fostering a stronger sense of national identity among KP’s youth. Revising curriculum guidelines to include explicit directives on cultural diversity and citizenship rights, emphasizing critical thinking in teacher training, and involving stakeholders in curriculum development processes can enhance the integration of national integrity discourse.